2015
DOI: 10.1093/ehjci/jev304
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional left atrial blood flow characteristics in patients with atrial fibrillation assessed by 4D flow CMR

Abstract: AimsTo apply 4D flow cardiac magnetic resonance (CMR) for the volumetric measurement of 3D left atrial (LA) blood flow to evaluate its potential to detect altered LA flow in patients with atrial fibrillation (AF) and to investigate associations of changes in systolic and diastolic LA flow with the current clinical risk score (CHA 2 DS 2 -VASc) used for the assessment of thromboembolic risk in AF. Methods and results4D flow CMR was performed in 40 patients with a history of AF (in sinus rhythm during CMR scan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 33 publications
5
58
0
Order By: Relevance
“…Previous studies by our group have already demonstrated good inter-observer variability good inter-observer agreement for measurements of mean LA velocity, peak LA velocity, and LA stasis 19, 21 . Future studies should also systematically test the reproducibility of the quantification of both LA and LAA flow and stasis.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies by our group have already demonstrated good inter-observer variability good inter-observer agreement for measurements of mean LA velocity, peak LA velocity, and LA stasis 19, 21 . Future studies should also systematically test the reproducibility of the quantification of both LA and LAA flow and stasis.…”
Section: Discussionsupporting
confidence: 55%
“…Reduced LA velocities have been associated with increased stasis and increased CHA 2 DS 2 -VASc score (p<0.043). [ 146 148 ]…”
Section: Clinical Evaluation Of Myopathymentioning
confidence: 99%
“…With regard to LA blood circulation, the thermal modeling assumes a 12-cm/s blood flow within the LA chamber, in accordance with measurements within AF patients in sinus rhythm. 27,28 In brief summary of this computational model, the fundamental assumed parameters are the idealized balloon-to-tissue interfacing boundaries and the thermodynamic heat (source and sink) exchanges, which then predict a progression of cold through the cardiac tissue and a resulting cellular response (and subsequent lesion formation in the manner of a PVI).…”
Section: Balloon-to-tissue Interactionsmentioning
confidence: 99%